Primary Spontaneous Pneumothorax in Children: A Literature Review - Ping-Yang Kuo; Bao-Ren Nong; Yung-Feng Huang; Yee-Husan Chiou (Pediatric Respirology and Critical Care Medicine)
Studies about primary spontaneous pneumothorax (PSP) in pediatric patients are not as many as in adult patients since the incidence of PSP is lower in children than in adults. There are evidence-based guidelines for the management of PSP in adults, whereas, in children, the approach of PSP is mainly extrapolated from the adult guideline. In this article, aspects of incidence rate, epidemiology, and pathophysiology, diagnosis, management, and recurrence rate about pediatric PSP are discussed.